2018
DOI: 10.1021/acs.analchem.8b03279
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Enhancement of NIR to UV Upconversion by a Nanoengineered Interface Consisting of NaYF4:Yb,Tm Nanoparticles and a Gold Nanotriangle Array for Optical Detection of Vitamin B12 in Serum

Abstract: A nanoengineered interface fabricated by self-assembly enables the online determination of vitamin B12 via a simple luminescence readout in serum without any pretreatment. The interplay of Tm3+-doped NaYF4 nanoparticles (UCNPs) and a gold nanotriangle array prepared by nanosphere lithography on a glass slide is responsible for an efficient NIR to UV upconversion. Hot spots of the gold assembly generate local electromagnetic-field enhancement, favoring the four-photon upconversion process at the low-power excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…The use of enhanced Raman spectroscopy to quantify VitB12 in multivitamin complexes was also successfully demonstrated by Ibáñez et al, who realized screen-printed Au electrodes to be used in the electrochemical SERS detection of VitB12 with an LoD of 4-7 nM [103]. Wiesholler et al realized active substrates depositing Tm 3+ -doped NaYF 4 nanoparticles on arrays of Au nanotriangles on glass substrates, which were used to detect VitB12 in serum analyzing the near-infrared (NIR) to ultraviolet (UV) luminescence upconversion, obtaining an LoD of 3.0 nmol L −1 [104].…”
Section: How To Monitor the Deficiency Of Vitb12: Involvement Of Nanomentioning
confidence: 99%
“…The use of enhanced Raman spectroscopy to quantify VitB12 in multivitamin complexes was also successfully demonstrated by Ibáñez et al, who realized screen-printed Au electrodes to be used in the electrochemical SERS detection of VitB12 with an LoD of 4-7 nM [103]. Wiesholler et al realized active substrates depositing Tm 3+ -doped NaYF 4 nanoparticles on arrays of Au nanotriangles on glass substrates, which were used to detect VitB12 in serum analyzing the near-infrared (NIR) to ultraviolet (UV) luminescence upconversion, obtaining an LoD of 3.0 nmol L −1 [104].…”
Section: How To Monitor the Deficiency Of Vitb12: Involvement Of Nanomentioning
confidence: 99%
“…12 In contrast to conventional uorescence probes (such as organic dyes, carbon nanomaterials, and semiconductor quantum dots), upconversion nanoparticles featuring large anti-Stokes shis, excellent chemical-and photo-stability, sharp multicolor emissions, and low toxicity have been regarded as a promising class of luminophores. 13 Up to now, a variety of functional materials including organic dyes, [14][15][16] noble metals, [17][18][19] quantum dots, [20][21][22] carbon nanomaterials, [23][24][25] and two-dimensional materials [26][27][28] has been employed to couple with upconversion nanoparticles to construct uorescence probes, realizing quantitative detection of inorganic ions, [29][30][31] pH, [32][33][34] small molecules, [35][36][37][38] and nucleic acids. [39][40][41][42] Most of the upconversion-based probes rely on the uorescence resonance energy transfer (FRET) process, in which a very short distance between the upconversion nanoparticles and absorbers is required.…”
Section: Introductionmentioning
confidence: 99%
“…High-efficiency fluorescent probes are an attractive tool for improving the sensitivity of optical-based biosensors. Previous studies have shown that an increase in the quantum yield of fluorescent probes can enhance the sensitivity of FL-based biosensors. The FL of probes can also be increased by inducing the surface plasmon of metals when the probes are near the metals [i.e., metal-enhanced fluorescence (MEF)]. , …”
Section: Introductionmentioning
confidence: 99%